Understanding the Motivations of Foster Caregivers at Animal Shelters - Roxy Ackerman; Brittany Watson; James Serpell; Chelsea L. Reinhard; Lauren Powell (Animals, 2023)
Foster care programs in animal shelters have been shown to benefit animals and shelters, but little is known about what motivates foster caregivers to volunteer. This cross-sectional study explored the motivations and expectations of 131 foster caregivers from five shelters within the United States who completed a pre-foster survey between March 2022 and March 2023. The most common motivations were animal- or community-based, such as the desire to provide an animal with love or do something positive for the community. Ordinal logistic regression models were used to investigate associations between caregivers’ motivations and their prior foster experience, pet ownership history, age, gender, and foster animal species. The 18- to 29-year-old caregivers were most likely to expect companionship (OR 5.18, 95% CI 1.79–15.04), emotional support (OR 4.25, 95% CI 1.40–12.89), and to meet other community members through fostering (OR 5.04, 95% CI 1.85–13.74). Male caregivers were less likely to foster for emotional support than females (OR 0.12, 95% CI 0.03–0.48), while dog caregivers (OR 2.23, 95% CI 1.04–4.76) and non-pet-owners (OR 2.66, 95% CI 1.17–6.05) had greater odds of expecting companionship. This study highlights the importance of animal- and community-related benefits for foster caregivers and provides useful direction for shelters wanting to increase recruitment to expand their foster care programs.